Criopreservação de sêmen humano : comparação entre método de congelação e tipos de envase - Cavalcante, Marcelo Borges (2004)
This research has as objective determines the best freezing method and storage of human semen, when compared the fast method with the slow method and the storage in 0,25ml straws with cryotubes of 2ml, using as variables the morphology and motility of the spermatozoa before and after the cryopreservation. It is an experimental study, laboratorial technique validation. It was developed in the Assisted Reproduction Center of Ceará. Eighteen semen samples from eighteen men were analyzed. The samples were submitted to the analysis of the morphology and motility previous the cryopreservation. It was still determined a spermatozoa motility curve in the first three hours. TEST-YOLK was used as cryoprotective media. After having added the TEST-YOLK media, the semen was divided in same parts and storage in cryotubes and straws. Half of the cryotubes and of the straws was cryopreserved by the fast method (RT and RP, respectively) and the other half by the slow method (LT and LP, respectively). The samples were thawed and analyzed the morphologies, as well as the motilities soon after the thawed and every hour for three hours. Statistical analysis was done by the SPSS program - Windows version 11.0.0. Motility of spermatozoa decrease after the cryopreservation, initial motility was 58,1% and motilities in the different treatments were 30,3% (LT), 21,1% (LP), 27% (RT) and 19,2% (RP). There was a significant decrease of the normal morphology after the cryopreservation, in relation to the initial morphology, but difference was not observed among the methods (RP=12,8%, RT=12,6%, LP=12,6% e LT=12,4%). The motility of LT method was closer than that obtained in the fresh semen. The method LT showed the best recovery of motile cells after freezing and thawing. There was not difference among the methods when appraised the morphology. Key-Word: Cryopreservation; Semen preservation; Spermatozoa; Reproduction.